SARS-CoV-2 remodels the Golgi apparatus to facilitate viral assembly and secretion. - Jianchao Zhang; Andrew Kennedy; Daniel Macedo de Melo Jorge; Lijuan Xing; Whitney Reid; Sarah Bui; Joseph Joppich; Molly Rose; Sevval Ercan; Qiyi Tang; David Ginsburg; Andrew W Tai; et al. (PLoS Pathogens, 2025)
The COVID-19 pandemic is caused by the enveloped virus SARS-CoV-2. Despite extensive investigation, the molecular mechanisms for its assembly and secretion remain largely elusive. Here, we show that SARS-CoV-2 infection induces global alterations of the host endomembrane system, including dramatic Golgi fragmentation. SARS-CoV-2 virions are enriched in the fragmented Golgi. Blocking endoplasmic reticulum (ER) to Golgi trafficking dramatically inhibits SARS-CoV-2 assembly and secretion without reducing viral genome replication. Significantly, SARS-CoV-2 infection down-regulates GRASP55 but up-regulates TGN46 protein levels. Surprisingly, GRASP55 expression reduces both viral secretion and spike number on each virion without affecting viral entry, while GRASP55 depletion displays opposite effects. In contrast, TGN46 depletion only inhibits viral secretion without affecting spike incorporation into virions. Taken together, we show that SARS-CoV-2 alters Golgi structure and function to modulate viral assembly and secretion, highlighting the Golgi as a potential therapeutic target for blocking SARS-CoV-2 infection.